Analisis terhadap Peranan Digital Marketing pada Media Sosial Perbankan: Studi Eksplorasi Penerimaan Konsumen - Suwarno Suwarno; Juven Gautama (STMIK Budi Darma, 2022)
Consumer perception through digital marketing has become one of the important factors in banking in the city of Batam to be known by marketers. Digital marketing at Rural Credit Banks (BPR) makes this possible to explore banner preferences for digital marketing, social media banking for digital marketing and prioritizing website banking for consumer perceptions through digital marketing from all banks in Batam City in part or thorough. The sample collection method is a quantitative approach (Quantitative Research) and qualitative with a purposive sampling technique on active banking customers in Batam City. This study reveals that the role of social media banking has a significant effect on digital marketing with an acceptance index of 69.5% which refers to the quite satisfactory category.